EPISTEMOLOGI POSITIVISME (BARAT) - Muhammad Abdillah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines the epistemology of positivism within the tradition of Western philosophy of science, focusing primarily on the contributions of Auguste Comte as its principal founder. Positivism emerged as a critical response to the dominance of metaphysical and theological explanations during the medieval period, offering a scientific approach grounded in empirical observation, verification, and the formulation of universal laws. By emphasizing principles such as empiricism, scientific objectivity, verification, and the rejection of metaphysics, positivism laid the foundation for modern scientific methodology and significantly influenced the development of various disciplines, including sociology, psychology, economics, and political science. This research employs a qualitative approach using library research methods, analyzing relevant academic journals and classical philosophical works related to epistemology and the philosophy of science. The findings indicate that positivism played a crucial role in shaping the paradigm of modern scientific rationality, despite receiving substantial criticism from scholars such as Karl Popper, Thomas Kuhn, and Max Weber. These critiques subsequently gave rise to post-positivist perspectives that acknowledge the role of social context, interpretation, and human subjectivity in scientific inquiry. In the contemporary era, positivism remains relevant, particularly in quantitative research, experimental sciences, and data-driven methodologies such as big data analysis. Therefore, the epistemology of positivism can be understood as a dynamic and evolving framework that continues to adapt to the changing landscape of modern scientific knowledge.